Eps8 is recruited to lysosomes and subjected to chaperone-mediated autophagy in cancer cells - Welsch, Thilo; Younsi, Alexander; Disanza, Andrea; Rodriguez, Jose Antonio; Cuervo, Ana Maria; Scita, Giorgio; Schmidt, Jan (Experimental cell research, 2010)
Eps8 controls actin dynamics directly through its barbed end capping and actin-bundling activity, and indirectly by regulating Rac-activation when engaged into a trimeric complex with Eps8-Abi1-Sos1. Recently, Eps8 has been associated with promotion of various solid malignancies, but neither its mechanisms of action nor its regulation in cancer cells have been elucidated. Here, we report a novel association of Eps8 with the late endosomal/lysosomal compartment, which is independent from actin polymerization and specifically occurs in cancer cells. Endogenous Eps8 localized to large vesicular lysosomal structures in metastatic pancreatic cancer cell lines, such as AsPC-1 and Capan-1 that display high Eps8 levels. Additionally, ectopic expression of Eps8 increased the size of lysosomes. Structure-function analysis revealed that the region encompassing the amino acids 184-535 of Eps8 was sufficient to mediate lysosomal recruitment. Notably, this fragment harbors two KFERQ-like motifs required for chaperone-mediated autophagy (CMA). Furthermore, Eps8 co-immunoprecipitated with Hsc70 and LAMP-2, which are key elements for the CMA degradative pathway. Consistently, in vitro, a significant fraction of Eps8 bound to (11.9±5.1%) and was incorporated into (5.3±6.5%) lysosomes. Additionally, Eps8 binding to lysosomes was competed by other known CMA-substrates. Fluorescence recovery after photobleaching revealed that Eps8 recruitment to the lysosomal membrane was highly dynamic. Collectively, these results indicate that Eps8 in certain human cancer cells specifically localizes to lysosomes, and is directed to CMA. These results open a new field for the investigation of how Eps8 is regulated and contributes to tumor promotion in human cancers.